Evaluation of the Structure and Functions of Home Gardens in Vavuniya District, Sri Lanka - Sharaniya, S. (Vavuniya Campus of the University of Jaffna, 2017)
Home gardens are conventional agro-forestry systems and characterized by the complexity of their structure and multiple functions. The objective of the study was to investigate the socioeconomic features of the study population and evaluation of the structure, functions and different methods of home garden. Primary data was collected from 30 randomly selected home gardens in Vavuniya district through questionnaire survey and field visits. The collected data were analyzed using Minitab 17. The majority of the farmers were females (60%) and remaining were males. The respondents of the study population were 21 to 75 years of age and around 53% of younger farmers have been involving in home gardening activities. The size of the home garden ranged from 0.05 to 1.5ha and size of the small household’s home gardens were less than 1ha. 70% of home gardens have more than 10 different plant species. Positive correlation was found between age of home garden owner –size of home garden and age of home garden owner – plant diversity (p<0.05). Farmers practiced different organic methods to control the pests. Ten percentage of the farmers apply organic productions, 13% use enemy plants (sun flower and Chrysanthemum), 43% use manual clearing and 34% of them use crop rotation to control the pest. 91% of the farmers have given the priority to their health and pesticide contamination than price of vegetables in market and farmers believed that organic pest control methods helped to protect the human health and prevent us from chronic health hazards. Home gardeners practiced different methods of home gardens.47% of the home gardeners raised bed method, 10% used pot method, 27% used packets method, 10% used bottle method and 6% tried vertical method. Around 67% of them buried their back yard and kitchen wastes to crops and 33% of them prepared compost. In case of home garden pattern- vegetable, medicinal, edible ornamental and multipurpose uses were recorded from the home garden respondents with an overall 40% of them had ornamental plants. This study recommends that creating awareness programs among the households about the importance of home garden plants for their routine life and its conservation.
Keywords: Home garden